EARLY RESULTS OF CAROTID ENDARTERECTOMY WITH LOCAL ANESTHESIA - Orçun Ünal (İstanbul Tıp Fakültesi Dergisi)
Objective: The gold standard treatment of carotid artery stenosis is performed with open surgical methods with carotid endarterectomy. Surgical treatment can be performed under general anesthesia or regional cervical block, locoregional combined anesthesia or local anesthesia. In this article, we aimed to present our experience of carotid endarterectomy under local anesthesia and its effects on mortality and morbidity in this patient group. Material and Method: A total of 417 endarterectomy procedures for carotid artery stenosis between 2002 and 2017 were retrospectively evaluated. All operations were performed by the same surgeon using the same standard technique under local infiltration anesthesia. Age, sex, risk factors, surgical indications, diagnostic methods, shunt use, duration of operation, neurological events, mortality and morbidity were evaluated in the operation group. The degree of stenosis was accepted as >70% in all patients for surgical indication. Results: The mean age of the patients was 64.6±11.3 years. The female / male ratio was 102/315. Smoking was the most important risk factor in all patients. Other risk factors were hypertension, diabetes, genetic factors and hyperlipidemia, respectively. The patients included in the study had different rates of ischemic heart disease, congestive heart failure, chronic obstructive pulmonary disease, peripheral artery disease and malignancy. 346 patients had various neurological symptoms ranging from transient ischemic attack due to carotid artery stenosis to persistent stroke, while the remaining 71 patients were asymptomatic. Mortality or neurological events did not occur during the operation. In-hospital mortality was seen in 3 patients: myocardial infarction in 1, intracranial hemorrhage in 1 and decompensated cardiac failure in one patient. Shunt usage was required in 31 (7%) patients. No major neurological event was encountered in any patient in the first postoperative month. Conclusion: Carotid endarterectomy can be performed safely with local anesthesia with increasing experience.